The role of fructose restriction in addition to dietary modifications for weight loss and lifestyle improvement, on fertility outcome and other markers of metabolic syndrome (MS), in obese women with polycystic ovarian syndrome (PCOS) - Weidemann, Annchen (Stellenbosch : Stellenbosch University, 2012)
Thesis (MNutr)--Stellenbosch University, 2012.